OPTIMIZATION OF MANPOWER PLANNING ON WORKLOAD PROFILE-BASED PRODUCTION FLUCTUATIONS - Al Ghifar, M Habibul Ichwan; Sugiono; Efranto, Remba Yanuar; Sholihah, Qomariyatus (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2025)
Workforce planning is a crucial aspect of optimizing labor efficiency in the Soya Department, particularly given fluctuating demand during peak, regular, and low seasons. This study aims to evaluate and recommend workforce planning using Workload Analysis (WLA) and Fault Tree Analysis (FTA) to identify workload imbalances and their root causes. The Process Activity Mapping (PAM) method is employed to analyze each general activity in detail. Initial findings indicate that certain areas experience workload overload, particularly in the warehouse section, where workloads exceed 125% during low season and 133.3% in regular and peak seasons. By adjusting manpower allocation, workload levels were successfully balanced to 100% (inload condition) across all seasons. Furthermore, FTA identified key factors contributing to workload imbalances, such as inefficient task distribution and process delays. The proposed manpower planning strategy significantly reduces dependency on overtime and outsourced labor, leading to increased productivity and cost efficiency. This research provides a structured framework for workforce optimization, offering practical insights for labor management in fluctuating demand environments.